MANAJEMEN MUTU LAYANAN AKADEMIK DALAM MENINGKATKAN PRESTASI AKADEMIK MADRASAH ALIYAH NEGERI 1 BANYUWANGI - Hidayati, Nur; Fadhilaturrohmah, Hilda (Jurnal Manajemen Pendidikan Islam Darussalam, 2022)
The objectives set in this research are: (1) To find out the Quality Management of Academic Services at MAN 1 Banyuwangi (2) To find out Academic Achievements at MAN 1 Banyuwangi (3) To find out the Quality Management of Academic Services in Improving Academic Achievement at MAN 1 Banyuwangi. The method used by the researcher is a qualitative approach with a descriptive type of research. Data collection techniques used 3 stages, namely observation, interviews, and documentation. The source the data that the researcher obtained is primary data in the form of observations related to the management of academic service quality in improving academic achievement, interviews with principals and teachers, as well as secondary data on documentation and archives of activities from the management of ma'had. Checking the validity of the data using triangulation, namely triangulation of theories, methods, and observers, Data analysis with three interactive models, namely data reduction, data presentation, and drawing conclusions. Research Results: quality management of academic services in improving academic achievement by providing several services, covers (1) Classroom learning services (2) service in the library (3) service in the laboratory (4) service in the administration room (5) services in the counseling room (6) place of worship service (7) service in the latrine (8) service in the UKS room (9) playground or sports services. Of the three kinds of academic achievement that is: (1) language ability (2) math skills (3) science ability, MAN 1 Banyuwangi students are superior in science skills. Student report cards and results from participating in competitions are a measure of academic achievement. And the function of the academic achievement assessment here is to determine the level of readiness of MAN 1 Banyuwangi students to take a certain level of education.